Coding for Change: Pelatihan Praktis Pemrograman dan Proyek AI Sederhana untuk Siswa SMA - Abror, A. Faiq; Ahmad Mubais (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2026)
The development of digital technology requires improved programming literacy and artificial intelligence understanding among high school students. However, information technology learning still focuses on application usage and lacks practical coding experience. This community service activity aimed to improve students’ basic Python programming skills and introduce simple AI through hands-on training using a project-based learning approach. The training materials included basic Python, mini projects (login system and calculator), Google Colab, and Canva AI. The results showed improvements in algorithmic thinking, the ability to develop simple programs, and increased student creativity and motivation. This training effectively enhanced digital literacy and technological competencies of high school students.